Bears [videorecording (DVD)] - Reilly, John C., 1965- ([publisher not identified], 2014)
Showcases a year in the life of a bear family as two young cubs are taught life's most important lessons. Set against an Alaskan backdrop teeming with life, their journey begins as winter comes to an end and the bears emerge from hibernation to face an exciting but risky world.